Learn JavaScript with p5.js Coding for Visual Learners - Arslan, Engin (Apress, 2018)
Learn coding from scratch in a highly engaging and visual manner using the vastly popular JavaScript with the programming library p5.js. The skills you will acquire from this book are highly transferable to a myriad of industries and can be used towards building web applications, programmable robots, or generative art. You'll gain the proper context so that you can build a strong foundation for programming. This book won't hinder your momentum with irrelevant technical or theoretical points. The aim is to build a strong, but not overly excessive knowledge to get you up and running with coding. If you want to program creative visuals and bring that skill set to a field of your your choice, then Learn JavaScript with p5.js is the book for you.